Genome-wide identification of GmEDS1 gene family members in soybean and expression analysis in response to biotic and abiotic stresses - Liu, Zhixian; Yang, Jiahui; Yan, Ziyu; Huang, Lexiang; Xing, Chengshun; Zhao, Miaoyu; Du, Haiping; He, Milan; Kong, Fanjiang; Liu, Baohui; Zhao, Xiaohui (Frontiers in Plant Science, 2025)
Enhanced Disease Susceptibility 1 (EDS1), a key regulator in plant defense responses, plays central roles in resistance to stresses. Therefore, the identification and characterization of soybean GmEDS1 family genes and verification of how these genes are associated with stresses are the focus of this study. We identified 11 GmEDS1 genes, which all have lipase-like and EP (EDS1-PAD4-specific) conserved domains, they are unevenly distributed across six chromosomes, including tandem repetitions. Whole-genome duplication and segmental duplication events were the main reason for GmEDS1 family expansion, and the family underwent purification selection during evolution. We detected 25 types of cis-regulatory elements, which enable GmEDS1s to respond to multiple signals. GmEDS1s are rapidly and strongly induced by drought, salt, the common cutworm, and soybean mosaic virus, indicating that they have important biological functions in coping with both abiotic and biological stresses. Furthermore, the expression levels of GmEDS1s differed between long-day and short-day conditions: it was very low under short-day conditions, which may increase the sensitivity of soybean to pathogens under short-day conditions. Overall, this study identified and characterized the members of the GmEDS1 gene family in the soybean genome, and determined that GmEDS1s respond to both abiotic and biotic stresses, providing new key genes for soybean breeders.